ANALISIS BUSINESS MODEL CANVAS PADA PERKEMBANGAN BISNIS SKINCARE MURIGLOW - Muhammad Kahfi Ridho Abghani; Suyatmi Suyatmi; Reza Widhar Pahlevi (SEGMEN: Jurnal Manajemen dan Bisnis, 2022)
The purpose of this study was to analyze the business model applied by Muriglow's skincare business. Muriglow is a producer of organic facial masks processed from fermented goat's kefir etawa milk containing lactobacillus which cleanses the face of dirt and stimulates collagen production in the skin, and many other benefits. The canvas business model elements use the nine elements of the canvas business model, namely customer segments, value proposition, channels, customer relationships, revenue streams, key resources, key activities, key partnerships and cost structure. The research method used is a qualitative descriptive analysis approach that is used to find factual information about problems or practices that occur in the field. The results showed that the market acquisition that Muriglow will do is to penetrate the cosmetics industry for men and this preparation has been planned under the name Muriglow for Men. The values offered are the fermented milk of Etawa goat kefir; The composition of the ingredients is 100% natural and safe for use by pregnant women, nursing mothers and children. Channels provided by social media (Instagram, FB, TikTok); E-commerce (Shopee, Tokopedia) and E-wallets (DANA, OVO). The relationships that are built are discounted prices with minimal spending; free shipping; buy 1 get 1 gift; special prices for resellers and giveaway. Its key activities are quality control, dosing & processing, packaging and marketing. Its business partners consist of Lab quality control, raw material suppliers, distributors, shipping expeditions. Muriglow plans to collaborate with production houses, especially in big cities to reduce the high cost of shipping and simplify Muriglow's supply network throughout Indonesia and will start from major cities on the island of Java.Keywords: Canvas Business Model, Skincare Business, and Business Value